Indo-Japan Relations: Deepening Bonhomie and New Security Equilibrium in the Asia Pacific - Singh, Sudhir (WILAYAH: The International Journal of East Asian Studies, 2014)
Bilateral relations between India and Japan have become one of the most significant interactions for the future. Though economically important, it is the strengthening of strategic relations which has increasingly assumed greater value since the beginning of the twenty-first century. Economically, East Asia is one of the most dynamic regions in the world, hence, most major powers are interested in its development. Managing relations with China and dealing with the rising stature of Beijing in the region is a cause of concern for both India and Japan. There are several persistent divergences between Japan and China which at any point of time can create a crisis. There are also serious divergences in the relations between India and China which often poses an obstruction to the development of stable relations. Hence, the main objective of both India and Japan is to maintain a balance of power in the region and prevent any one country from becoming too dominant. It is also true for the larger canvass of Asia-Pacific as Asian countries want stronger Indo-Japan relations within a multilateral framework that includes the United States.